Timing design for geosynchronous SAR. Issue 10 (1st May 2016) - Li, Caipin; He, Mingyi
Abstract : Compared with low‐earth‐orbit synthetic aperture radar (SAR), geosynchronous SAR (GEO SAR) due to the long synthetic aperture time and the sensitive effect of the earth's rotation, has great range migration in its echo and the extension of the receiving time window, resulting in the conventional timing design unusable. To solve this problem, a timing design method for GEO SAR is proposed in which the range migration is taken into consideration to avoid loss of echo. The equations and steps of the timing design are given in detail and in addition the range ambiguity and the azimuth ambiguity for GEO SAR are also discussed. Simulated results have verified the validity of the proposed timing design method for GEO SAR.